Patterns of Self-Medication with Medicinal Plants and Related Adverse Events - A South American Survey - Consolini, Alicia Elvira (2010)
Medicinal plants are useful as a natural therapy to treat minor illnesses, as gastrointestinal disorders or as topic antiinflammatories. Also, they have been increasingly used as a coadjuvant in cronic diseases as hypertension, diabetes or hyperlipidemias. Nevertheless, many of the plants have active principles which are contraindicated or need precaution in certain illnesses as coagulation disorders or in certain states as pregnancy or breastfeeding. In this review we had compiled the side-effects, precautions and interactions with other medicines of many plants which are used in self-medication in our region. A previous population study gave us information on the consumption of medicinal plants in 73 pharmacies of the Buenos Aires province, in Argentina. During a period of one year, there were 37102 self-medicated plants, while only 1532 were prescribed by the physician. Among the most frequently selfmedicated plants are Malva sylvestris L., Matricaria chamomile L, and Quassia amara. Among the most frequently prescribed are also "malva" and "chamomile", Tilia cordata Mill. and Valeriana officinalis. Based in the most consumed medicinal plants in our region, we reviewed the risks of such plants and the precautions that should be taken for a rational use. Also, we detected 15 adverse-reactions reported by the pharmacists through a pharmaceutical vigilance program, which are described and analyzed here. The results of the study and other reports suggest that adverse reactions of herbal medicines could be avoided if preventing self-medication, and taking into consideration possible contraindications and interactions.